Global citrus root microbiota unravels assembly cues and core members - Lombardo, Monia F.; Zhang, Yunzeng; Xu, Jin; Trivedi, Pankaj; Zhang, Pengfan; Riera, Nadia; Li, Lei; Wang, Yayu; Liu, Xin; Fan, Guangyi; Tang, Jiliang; Coletta-Filho, Helvécio D.; et al. (Frontiers in Microbiology, 2024)
Citrus is one of the most important fruit crops worldwide, and the root-associated microbiota can have a profound impact on tree health and growth. In a collaborative effort, the International Citrus Microbiome Consortium investigated the global citrus root microbiota with samples collected from nine citrus-producing countries encompassing all six continents. We analysed the 16S rDNA and ITS2 amplicon sequencing data. Ten predominant prokaryotic phyla, containing nine bacterial phyla including Proteobacteria, Actinobacteria, Acidobacteria, and Bacteroidetes and one archaeal phylum (Thaumarchaeota), and multiple fungal phyla including Ascomycota and Basidiomycota were identified in the citrus root samples. Compared with the microbial communities from the corresponding rhizosphere and bulk soil samples from the same trees, the root prokaryotic and fungal communities were less diverse and complex but more modular than the rhizosphere ones. 30 root-enriched and 150 root-depleted genera in bacterial community were identified, whereas 21 fungal genera were enriched, and 147 fungal genera were depleted in the root niche compared with the rhizosphere. We have conducted citrus genotype-based group-wise comparisons which revealed that the citrus genotype had a significant impact on the root prokaryotic and fungal communities. In addition, we have identified the core root prokaryotic genera comprising Acidibacter, Allorhizobium, Bradyrhizobium, Chitinophaga, Cupriavidus, Devosia, Dongia, Niastella, Pseudomonas, Sphingobium, Steroidobacter and Streptomyces, and the core fungal genera including Acrocalymma, Cladosporium, Fusarium, Gibberella, Mortierella, Neocosmospora and Volutella. The potential functions of these core genera of root microbiota were also predicted. Overall, this study provides new information about assemblage of microbial communities and core members of citrus root microbiota in a broad biogeographical sampling. This study is valuable in manipulating the root microbiota for plant growth and health.